Co-opetition: the ability to co-operate and compete together - Mirzabeiki, Vahid; Humphries, Andrew; Wilding, Richard D. (The Chartered Institute of Logistics and Transport, 2017)
In 1996, logistics professionals began to become excited about a new supply chain paradigm. Co-opetition – a combination of co-operation and competition – was the title of a best-selling business book by two American academics, Adam M Brandenburger and Barry J Nalebuff, from Harvard and Yale business schools respectively. As the name implies, the basis of the idea is collaboration between competitors, a concept that is not as bizarre as one might expect. Why? Because those businesses with supply chain challenges and requirements that will be closest to a given business’s own supply chain challenges and requirements will generally be its competitors. In the motor industry, for instance, tyre, battery and exhaust system manufacturers and distributors must deliver to the same dealerships and aftermarket retail outlets; and grocery manufacturers must deliver to the same supermarket regional distribution centres, wholesalers, and retail outlets. In such circumstances, pointed out Brandenburger and Nalebuff, co-opetition made a lot of sense. When it comes to logistics and transport, there have been fewer high-profile examples, at least in terms of direct co-opetition, as opposed to firms collaborating through the shared and co-ordinated use of a third-party logistics provider. This article explores the Co-opetition between Nestle and Pladis within logistics. Barriers and wider lessons are outlined.